2018
DOI: 10.1007/jhep09(2018)141
|View full text |Cite
|
Sign up to set email alerts
|

A vertex operator algebra construction of the colour-kinematics dual numerator

Abstract: We derive a vertex operator based expression for the kinematic numerators of Yang-Mills amplitudes by applying the momentum kernel formalism to open string amplitudes. The expression involves an α -weighted commutator induced by the monodromy relations between the colour ordered Yang-Mills amplitudes, which mirrors the α deformed colour structure observed in open string and semi-abelian Ztheory. The kinematic algebra given by this construction contains the Lie algebra of diffeomorphism as an obvious sub-algebr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 124 publications
(190 reference statements)
0
35
0
Order By: Relevance
“…Effective non-gravitational theories for which a double-copy construction is known include the Dirac-Born-Infeld and the special Galileon theories, as well as the nonlinear sigma model [38,39,40,41,42,43,44]. Double-copy structures have also been identified for various string-theory amplitudes, [45,46,47,48,49,50,51,52,53], within the Cachazo-He-Yuan formalism [54,55,56,57,58], in the context of ambitwistor string theories [59], and at the level of linearized supermultiplets [60,61,62,63,64].…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…Effective non-gravitational theories for which a double-copy construction is known include the Dirac-Born-Infeld and the special Galileon theories, as well as the nonlinear sigma model [38,39,40,41,42,43,44]. Double-copy structures have also been identified for various string-theory amplitudes, [45,46,47,48,49,50,51,52,53], within the Cachazo-He-Yuan formalism [54,55,56,57,58], in the context of ambitwistor string theories [59], and at the level of linearized supermultiplets [60,61,62,63,64].…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…It is curious to note that the objects that the kinematic Lie algebra should compute, the kinematic BCJ numerators, are under better control than the algebra itself. Numerators that manifest the color-kinematics duality have been constructed at any multiplicity for tree-level amplitudes in pure Yang-Mills theory [20][21][22][23][24][25][26][27]. For supersymmetric Yang-Mills theory, it has been observed that a recursive construction similar to Berends-Giele recursion [28] can be used to generate BCJ numerators after using appropriate non-linear gauge transformations [23].…”
Section: Introductionmentioning
confidence: 99%
“…[70]), that yields local Yang-Mills numerators from a closed algebra. For non-local numerators there exists an algebraic construction using string vertex operators [27].…”
Section: Introductionmentioning
confidence: 99%
“…This technique, together with unitarity methods [34], has allowed for studies of the ultraviolet behaviour of supergravity theories. At tree level, the colour-kinematics duality is well-established, even if its algebraic origin remains to be satisfactorily explained; see, for instance, the constructions [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. The status of the loop-level conjecture is unclear, however.…”
mentioning
confidence: 99%